2016
DOI: 10.2525/ecb.54.79
|View full text |Cite
|
Sign up to set email alerts
|

Twofold Increase in Strawberry Productivity by Integration of Environmental Control and Movable Beds in a Large-scale Greenhouse

Abstract: 2) with a movable bed system, the fruit yield per unit land area achieved was 10.7 kg m 2 (10.7 t / 10 a), which represented a more than two-fold increase in yield compared with that attained in a conventional stationary bed system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…In an effort to avoid the down-regulation of photosynthesis, previous studies have shown that the down-regulation of leaf photosynthesis in tomato plants only occurred when the number of sinks was considerably reduced under elevated CO2 treatment (Qian et al, 2012). Furthermore, Hidaka et al (2016) suggested that adjusting the timing of initiation of CO2 enrichment to correspond with the sink strength of plants can increase fruit yield. For this new local CO2 enrichment system, further studies are necessary to adjust the timing and strength of CO2 enrichment and to promote photosynthate translocation to sink organs in order to increase fruit yield.…”
Section: Performance and Effectiveness Of The Systemmentioning
confidence: 99%
“…In an effort to avoid the down-regulation of photosynthesis, previous studies have shown that the down-regulation of leaf photosynthesis in tomato plants only occurred when the number of sinks was considerably reduced under elevated CO2 treatment (Qian et al, 2012). Furthermore, Hidaka et al (2016) suggested that adjusting the timing of initiation of CO2 enrichment to correspond with the sink strength of plants can increase fruit yield. For this new local CO2 enrichment system, further studies are necessary to adjust the timing and strength of CO2 enrichment and to promote photosynthate translocation to sink organs in order to increase fruit yield.…”
Section: Performance and Effectiveness Of The Systemmentioning
confidence: 99%
“…In particular, supplemental lighting should be an effective way of achieving this under conditions which provide insufficient light. For example, Hidaka et al (2016) achieved a twofold increase in strawberry yield through the combined application of LED lighting and CO 2 enrichment. As similar effects on crop growth and yield have been demonstrated previously by a variety of other studies (Martine et al, 1990;Andre et al, 1996;Demers et al, 1998;Hidaka et al, 2013), these techniques should be considered as essential for crop production in protected horticulture.…”
Section: Introductionmentioning
confidence: 99%
“…Control of atmospheric carbon dioxide, known to increase strawberry yield, is used widely in strawberry cultivation greenhouses (Lieten, 1997;Wada et al, 2010). Temperature management is also important for obtaining high yields of strawberries (Hidaka et al, 2016). On the basis of the environmental information in greenhouses, producers can continuously control the environment.…”
Section: Introductionmentioning
confidence: 99%